Photoinitiator, preparation method of photoinitiator, composition containing photoinitiator and application of photoinitiator
By using a new photoinitiator with an α-carbonyl structure in 3D printed composite ceramic materials, the problems of yellowing and inducing low efficiency in the polymerization process are solved, the density and performance of the material are improved, and the requirements of clinical anti-staining performance are met.
Patent Information
- Application Number
- CN202411973988.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The photoinitiators of existing 3D printed composite ceramic materials are prone to yellowing during the polymerization process, causing low induction efficiency, resulting in poor density, strength, hardness and molding accuracy of the material, and the anti-staining performance does not meet clinical requirements.
A new photoinitiator is provided, whose structure contains an α-carbonyl structure, preferably without a phenyl-phosphorus chemical bond. By optimizing its structure and preparation method, the degree of polymerization reaction is improved, thereby enhancing the density and properties of the material.
It improves the density of the organic and inorganic dual network structure, enhances the strength, hardness and molding accuracy of the material, improves the anti-staining performance, and meets the requirements of clinical applications.
Smart Images

Figure CN119775315A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dental restoration, and in particular to a photoinitiator and a preparation method thereof, and a composition and application thereof. Background Art
[0002] As a manufacturing technology with significant digital features, 3D printing technology has not only become a link in the oral digital processing chain, but also linked the oral diagnosis, design, and production processes together through data flow, forming a fully digital process for dental product processing. In recent years, mainstream dental processing plants have been undergoing digital transformation, which has promoted the development of 3D printed dental materials.
[0003] 3D printed composite ceramic materials can be used to make crowns, bridges, veneers, inlays and other restorations. Due to its low production cost and short production time, it is defined as an ideal material to replace CAD / CAM resin-based ceramic materials. 3D printed composite ceramic materials are usually organic and inorganic composite materials formed by mixing organic resin as the matrix, inorganic ceramic fillers as the reinforcement, and adding photoinitiators and other additives.
[0004] Due to the high content of inorganic fillers, the degree of light-induced polymerization in 3D printed composite ceramic materials is lower than that of thermally-induced polymerization in CAD / CAM resin-based ceramic materials, making the organic-inorganic double network structure of the material loose after polymerization. This makes it easy for water in saliva to enter the organic network of the material, causing the incompletely polymerized resin monomers and some chemical components in the material to be released from the material into the oral environment, resulting in the risk of secondary caries caused by marginal microleakage, the occurrence of fracture and detachment of restorations due to the decrease in mechanical properties of the material, the decrease in molding accuracy of the material after water absorption, resulting in decreased wearing comfort, and even a decrease in the ability to resist food pigment staining, resulting in a deterioration in aesthetic effects.
[0005] Moreover, currently commercialized photoinitiators that can be used in the 385 / 405nm band generally contain large conjugated structures (chromophores) to enable them to obtain good light absorption capabilities. However, when the amount is small, the degree of polymerization reaction is low, the organic-inorganic double network structure is loose, and the product strength, hardness and molding accuracy are poor. When the amount of photoinitiator is increased, although the density of the double network is improved, the large conjugated structure will cause the solubility of the photoinitiator in the monomer to deteriorate, resulting in poor color stability of the product and the color difference value of anti-staining does not meet clinical requirements.
[0006] Therefore, how to improve the density of the organic-inorganic dual network structure while ensuring safety, aesthetics and comfort is the key to whether 3D printed composite ceramic materials can replace CAD / CAM resin-based ceramic materials. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photoinitiator and a preparation method thereof, as well as a composition and application containing the same. By optimizing the structure of the initiator, the problems of easy yellowing and low initiation efficiency in the prior art are avoided, and by compounding the components of the composition, the strength, hardness and molding accuracy of the product are improved.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a photoinitiator, the structural formula of the photoinitiator is shown in formula (1):
[0010]
[0011] In formula (1), X is a halogen element or hydrogen, R1 and R2 are each independently any one of substituted and / or substituted phenyl and / or hydrocarbon groups, for example, any one of a hydrocarbon group having 1 to 15 carbon atoms, a toluyl group, an ethylphenyl group, a phenyl group or a propylphenyl group, or a combination of at least two thereof, wherein the number of carbon atoms may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, etc., and Y1 and Y2 are each independently any one of a branched or straight-chain hydrocarbon group.
[0012] Compared with the existing commercially available photoinitiators, the photoinitiator provided by the present invention has an α-carbonyl structure, and therefore has the advantages of being easily compatible with the resin system and having a high initiation efficiency. Since the photoinitiator provided by the present invention has a short initiation efficiency, it can increase the degree of polymerization reaction, thereby ultimately increasing the density of the dental restoration material; preferably, it does not have a phenyl-phosphorus chemical bond structure, and therefore has biosafety and can be used as a dental material.
[0013] Preferably, X in the formula (1) comprises any one of fluorine, bromine, chlorine or iodine, preferably fluorine.
[0014] Preferably, R1 and R2 are each independently a substituted and / or unsubstituted phenyl group, preferably p-methylphenyl group.
[0015] The present invention preferably uses p-methylphenyl, which has a biosafety effect, that is, after the free radical initiation is completed, benzoic acid and its derivatives are generated, which are easily excreted from the human body without the problem of toxic residues, and can be well applied in the field of dental materials.
[0016] Preferably, Y1 and Y2 are each independently an alkyl group having 1 to 5 carbon atoms, for example, 1, 2, 3, 4 or 5 carbon atoms, preferably a methyl group.
[0017] In a second aspect, the present invention provides a method for preparing the photoinitiator according to the first aspect, the preparation method comprising:
[0018] Oxalyl chloride and halogenated benzene undergo a first reaction to prepare p-halogenated benzoyl ester; the p-halogenated benzoyl ester undergoes a second reaction with the structure represented by formula (2) to prepare the photoinitiator of the structure represented by formula (1).
[0019]
[0020] In formula (2), R3 is an aromatic hydrocarbon group.
[0021] The preparation process provided by the present invention can realize the preparation of the photoinitiator in formula (1), and the preparation process has the advantages of simple operation, green environmental protection, and broad application prospects.
[0022] Preferably, the oxalyl chloride ester is oxalyl chloroformate.
[0023] Preferably, the p-halobenzoyl ester is p-halobenzoyl formate.
[0024] Preferably, in the structure represented by formula (2), R3 is any one of substituted phenyl, benzyl or phenethyl, or a combination of at least two thereof.
[0025] Preferably, the mass ratio of oxalyl chloride to halogenated benzene is 1.02 to 1.6:1, for example, it can be 1.02:1, 1.09:1, 1.15:1, 1.22:1, 1.28:1, 1.35:1, 1.41:1, 1.48:1, 1.54:1 or 1.6:1, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0026] Preferably, the mass ratio of the structure represented by formula (2) to the p-halogenated benzoyl ester is 2.3 to 3.2:1, for example, it can be 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1 or 3.2:1, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0027] Preferably, the first reaction is carried out under the catalysis of a catalyst.
[0028] Preferably, the catalyst comprises aluminum trichloride.
[0029] Preferably, the mass ratio of aluminum chloride to halogenated benzene is 1.4 to 1.75:1, for example, it can be 1.40:1, 1.44:1, 1.48:1, 1.52:1, 1.56:1, 1.6:1, 1.64:1, 1.68:1, 1.72:1 or 1.75:1, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0030] Preferably, the first reaction comprises: mixing halogenated benzene, aluminum chloride and a first solvent to obtain a first mixed solution, mixing oxalyl chloride and a second solvent to obtain a second mixed solution, and dropping the second mixed solution into the first mixed solution and simultaneously performing a first stirring to perform a first stage reaction, and after the dropwise addition is completed, heating and continuing the second stage reaction.
[0031] Preferably, the first solvent comprises dichloromethane.
[0032] Preferably, the second solvent comprises dichloromethane.
[0033] Preferably, the dripping rate of the second mixed liquid is 4 to 5 mL / s, for example, it can be 4 mL / s, 4.2 mL / s, 4.3 mL / s, 4.4 mL / s, 4.5 mL / s, 4.6 mL / s, 4.7 mL / s, 4.8 mL / s, 4.9 mL / s or 5 mL / s, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0034] Preferably, the reaction time of the second stage is 3 to 5 h, for example, 3 h, 3.3 h, 3.5 h, 3.7 h, 3.9 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h or 5 h, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] Preferably, the temperature of the first stage reaction is 2-10°C, for example, it can be 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C or 10°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0036] Preferably, the temperature of the second stage reaction is 20-35°C, for example, it can be 20°C, 22°C, 24°C, 25°C, 27°C, 29°C, 30°C, 32°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0037] Preferably, after the first reaction, the preparation method further comprises: separating, washing and drying the material after the first reaction.
[0038] Preferably, the separation comprises: mixing the first reacted material with water and performing liquid-liquid phase separation to obtain a first aqueous phase and a first organic phase. Extracting organic matter in the first aqueous phase with dichloromethane, and mixing the obtained second extracted organic phase with the first organic phase to obtain an organic product;
[0039] Preferably, the washing comprises: washing the organic product with a saturated sodium chloride solution.
[0040] Preferably, the drying comprises drying the organic product using anhydrous sodium sulfate.
[0041] Preferably, the second reaction comprises: directly mixing the organic product with the structure represented by formula (2), and removing the solvent and purifying to obtain the photoinitiator having the structure represented by formula (1).
[0042] Preferably, said removing the solvent comprises distillation, preferably distillation under reduced pressure.
[0043] Preferably, the purification comprises purification using a silica gel chromatography column.
[0044] In a third aspect, the present invention provides a composition, comprising the photoinitiator described in the first aspect and / or a photoinitiator prepared by the method for preparing the photoinitiator described in the second aspect.
[0045] Since the composition provided by the present invention contains the above-mentioned photoinitiator, it will not turn yellow during the photopolymerization process, and has high initiation efficiency, and can significantly improve the compactness of the organic-inorganic double network structure.
[0046] Preferably, the composition further comprises oligomers, monomers and fillers.
[0047] Preferably, the mass fraction of the oligomer in the composition is 5-20%, for example, it can be 5%, 7%, 9%, 10%, 12%, 14%, 15%, 17%, 19% or 20%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0048] In addition to the monomers, the composition provided by the present invention preferably contains oligomers. The presence of the oligomers can combine the various components of the product together, giving it plasticity and curing properties, and having the effect of enhancing mechanical properties.
[0049] Preferably, the mass fraction of the monomer in the composition is 12-30%, for example, it can be 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0050] Preferably, the mass fraction of the photoinitiator in the composition is 0.01-4%, for example, it can be 0.01%, 0.46%, 0.9%, 1.34%, 1.79%, 2.23%, 2.67%, 3.12%, 3.56% or 4%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0051] In the present invention, the amount of photoinitiator added is preferably controlled within the above range, which can prevent the cured product from yellowing easily, and the aesthetics caused by the deterioration of color stability and staining resistance, while avoiding the problem of low degree of polymerization reaction and loose double network resulting in poor strength and hardness performance.
[0052] Preferably, the mass fraction of filler in the composition is 42-80%, for example, it can be 42%, 47%, 51%, 55%, 59%, 64%, 68%, 72%, 76% or 80%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0053] Preferably, the composition further comprises additives.
[0054] Preferably, the mass fraction of the additive in the composition is 1-4%, for example, it can be 1%, 1.1%, 1.2%, 1.3%, 1.34%, 1.79%, 2.23%, 2.67%, 3.12%, 3.56% or 4%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0055] Preferably, the oligomer comprises an oligomeric acrylate derivative.
[0056] Preferably, the oligomer comprises any one or a combination of at least two of polyurethane acrylate, epoxy acrylate, dimethacrylate urethane, bisphenol A-glycidyl dimethacrylate, ethoxy bisphenol A dimethacrylate or bisphenol A glycerol dimethacrylate, wherein typical but non-limiting combinations are a combination of polyurethane acrylate and epoxy acrylate, a combination of dimethacrylate urethane and epoxy acrylate, a combination of polyurethane acrylate and dimethacrylate urethane, and a combination of phenol A-glycidyl dimethacrylate and epoxy acrylate.
[0057] Preferably, the monomer comprises a free radical acrylate monomer having at least one functional group, preferably comprising any one of a monofunctional free radical acrylate monomer, a difunctional free radical acrylate monomer or a trifunctional free radical acrylate monomer or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of a monofunctional free radical acrylate monomer and a difunctional free radical acrylate monomer, a combination of a trifunctional free radical acrylate monomer and a difunctional free radical acrylate monomer, and a combination of a monofunctional free radical acrylate monomer and a trifunctional free radical acrylate monomer.
[0058] Preferably, the monofunctional free radical acrylate monomer includes any one of cyclotrimethylolpropane type acrylate, lauric acid acrylate, acryloyl morpholine, dicyclopentenyl acrylate, isobornyl acrylate, ethoxylated phenoxy acrylate or ethoxylated nonylphenol acrylate, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of cyclotrimethylolpropane type acrylate and lauric acid acrylate, a combination of acryloyl morpholine and lauric acid acrylate, a combination of cyclotrimethylolpropane type acrylate and acryloyl morpholine, a combination of dicyclopentenyl acrylate and lauric acid acrylate, a combination of isobornyl acrylate and lauric acid acrylate, and a combination of ethoxylated nonylphenol acrylate and isobornyl acrylate.
[0059] Preferably, the bifunctional free radical acrylate monomer includes any one of ethoxybisphenol A dimethacrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, triethylene glycol dimethacrylate, tripropylene glycol diacrylate, tricyclodecane dimethanol diacrylate or dipropylene glycol diacrylate, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of ethoxybisphenol A dimethacrylate and tetraethylene glycol dimethacrylate, a combination of 1,6-hexanediol dimethacrylate and tetraethylene glycol dimethacrylate, a combination of ethoxybisphenol A dimethacrylate and tripropylene glycol diacrylate, and a combination of tricyclodecane dimethanol diacrylate and tripropylene glycol diacrylate.
[0060] Preferably, the trifunctional free radical acrylate monomer comprises any one of trimethylolpropane triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, pentaerythritol triacrylate or ethoxylated trimethylolpropane triacrylate, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of trimethylolpropane triacrylate and propoxylated glycerol triacrylate, a combination of trimethylolpropane trimethacrylate and propoxylated glycerol triacrylate, a combination of tris(2-hydroxyethyl)isocyanuric acid triacrylate and trimethylolpropane trimethacrylate, a combination of trimethylolpropane triacrylate and tris(2-hydroxyethyl)isocyanuric acid triacrylate, and a combination of pentaerythritol triacrylate and propoxylated glycerol triacrylate.
[0061] Preferably, the filler comprises an inorganic filler.
[0062] Preferably, the inorganic filler is a silane-modified filler.
[0063] Preferably, the inorganic component in the inorganic filler includes any one of barium glass powder, feldspar powder, quartz powder, sodium aluminum silicate powder or zirconium dioxide powder, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of barium glass powder and feldspar powder, a combination of quartz powder and feldspar powder, a combination of barium glass powder and quartz powder, a combination of sodium aluminum silicate powder and feldspar powder, and a combination of barium glass powder and zirconium dioxide powder.
[0064] Preferably, the additive comprises any one of a polymerization inhibitor, a defoaming agent, a fluorescence imparting agent, an indicator, a viscosity modifier or a pigment, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of a polymerization inhibitor and a defoaming agent, a combination of an indicator and a defoaming agent, a combination of a polymerization inhibitor and an indicator, a combination of a viscosity modifier and a defoaming agent, and a combination of a polymerization inhibitor and a pigment.
[0065] Preferably, the preparation of the composition comprises: mixing the raw materials of the composition, stirring and mixing under light-proof conditions, to obtain the composition.
[0066] Preferably, the stirring speed of the stirring and mixing is 1000-3000 rpm, for example, it can be 1000 rpm, 1220 rpm, 1440 rpm, 1660 rpm, 1880 rpm, 2110 rpm, 2330 rpm, 2550 rpm, 2770 rpm or 3000 rpm, but is not limited to the listed values, and other values not listed in this range are also applicable.
[0067] Preferably, the stirring and mixing time is 0.5 to 2 h, for example, 0.5 h, 0.7 h, 0.9 h, 1 h, 1.2 h, 1.4 h, 1.5 h, 1.7 h, 1.9 h or 2 h, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0068] Preferably, the raw materials of the mixed composition include: first mixing monomers and photoinitiators, and then adding oligomers and fillers in sequence.
[0069] Preferably, an additive is added between the oligomer and the filler in the raw materials of the mixed composition.
[0070] In a fourth aspect, the present invention provides a use of the composition described in the first aspect in a dental restorative material.
[0071] Preferably, the composition is used to prepare ceramic crown and bridge materials.
[0072] It is worth noting that through the composition combination of the composite, the obtained composite ceramic crown and bridge composition has a high degree of polymerization reaction, high strength, hardness and molding accuracy; low water absorption value and anti-staining color difference value, which can meet the requirements of printed composite ceramic crowns and bridges for clinical wearing.
[0073] Preferably, the preparation comprises: curing the composition to obtain a ceramic crown and bridge material.
[0074] Preferably, the curing comprises 3D printing light curing.
[0075] Preferably, the wavelength of the light source used in the 3D printing light curing is 385nm and / or 405nm.
[0076] Preferably, the temperature of the printing chamber in the 3D printing light curing is 20-40°C, for example, it can be 20°C, 23°C, 25°C, 27°C, 29°C, 32°C, 34°C, 36°C, 38°C or 40°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0077] Preferably, the curing further includes secondary curing after 3D printing light curing.
[0078] Preferably, the secondary curing comprises: 3D printing light-cured material at a light power of 50 to 200 mw / cm 2 The secondary curing is carried out under the conditions of, for example, 50mw / cm 2 、67mw / cm 2 、84mw / cm 2 、100mw / cm 2 、117mw / cm 2 、134mw / cm 2 、150mw / cm 2 、167mw / cm 2 、184mw / cm 2 or 200mw / cm 2 The above values are not limited to the above values, and other values not listed in the above values are also applicable.
[0079] Preferably, the secondary curing time is 10 to 20 minutes, for example, it can be 10 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0080] Compared with the prior art, the present invention has at least the following beneficial effects:
[0081] (1) The photoinitiator provided by the present invention can reduce the problems of yellowing and low initiation efficiency that occur in commercially available initiators during photopolymerization, and improve the compactness of the organic-inorganic dual network structure;
[0082] (2) The composition provided by the present invention is a high-density double-network printed composite ceramic crown and bridge composition. By combining specific amounts of oligomers, monomers, photoinitiators and inorganic powders, the obtained composite ceramic crown and bridge composition has a high degree of polymerization reaction and high strength, hardness and molding accuracy. Specifically, under preferred conditions, the flexural strength is above 200 MPa, the flexural modulus is above 8.5 GPa, the fracture toughness is above 2.51 MPa·m1 / 2, and the Vickers hardness is above 33.88 HV; the water absorption value and anti-staining color difference value are low, and the water absorption value is low, which is only 17.08 μg / mm 3 The solubility value is only 1.71μg / mm 3 The anti-staining difference is within 1.8, and it has strong anti-staining ability, which can meet the requirements of printed composite ceramic crowns and bridges for clinical wearing, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 It is the infrared spectrum of the photoinitiator A in the present invention.
[0084] Figure 2 It is the mass spectrum of the photoinitiator A in the present invention. DETAILED DESCRIPTION
[0085] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0086] It should be understood that the terms "first", "second", etc. are used for descriptive purposes only and should not be understood to indicate or imply relative importance or implicitly indicate the number of technical features indicated. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0087] The structural formula of photoinitiator A is shown in formula (3):
[0088]
[0089] The preparation method of the photoinitiator A comprises the following steps:
[0090] 26.88g of fluorobenzene and 46.69g of aluminum chloride were dissolved in 1.5L of dichloromethane to obtain a first mixed solution, and then the first mixed solution was placed in a 5°C water bath. 27.44g of oxalyl chloroformate was dissolved in 0.7L of dichloromethane to obtain a second mixed solution, and the second mixed solution was dripped into the first mixed solution at a rate of 4.5mL / second and the first stirring of 300rpm was carried out simultaneously to carry out the first stage reaction. After the addition was completed, the temperature was raised to room temperature (25°C) and the second stage reaction was continued for 4 hours. After the first reaction was completed, the material after the first reaction was poured into 7L of deionized water at 5°C and stirred, the water layer was separated from the organic layer, and the water layer was extracted with dichloromethane, the organic layers were combined, washed with saturated brine, and then dried over anhydrous sodium sulfate to obtain an organic product. The organic product was uniformly mixed with 62.16 g of (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, the solvent was removed by distillation under reduced pressure, and the mixture was purified by silica gel column chromatography to obtain light yellow solid p-fluorobenzoylformate-acylphosphine oxide, with a total yield of 61.9% by mass fraction.
[0091] The infrared spectrum and mass spectrum of the photoinitiator A prepared above are as follows: Figure 1-2 As shown, from Figure 1 It can be seen that infrared IR: at 3085cm -1 、3066cm -1 and 3030cm -1 =CH stretching vibration absorption at 1495cm -1 and 1450cm -1 The benzene ring skeleton vibration at 3000cm-1 indicates that the analyte contains benzene ring; the CH stretching vibration of saturated carbon at 3000cm-1 and the CH stretching vibration at 1430cm-1 indicate that the analyte contains benzene ring. -1 and 1320cm -1 The absorption peak at 1770-1720cm -1 A broad and strong peak appears, which is the characteristic absorption peak of the ester group; 1740cm -1 and 1690cm -1 The symmetrical double shoulder peaks are two adjacent C=O characteristic absorption peaks; 1210cm -1 and 1030cm -1 is the COC stretching vibration absorption peak; Figure 2 It can be seen that the mass spectrum MS: m / z105 is a characteristic peak of C6H5CO+, m / z39, 51, and 77 peaks indicate that the analyte contains a benzene ring, m / z28 indicates that it contains a carbonyl group, and m / z15 indicates that it contains a methyl group. This shows that the obtained light yellow solid is indeed p-fluorobenzoylformate-acylphosphine oxide.
[0092] The structural formula of photoinitiator B is shown in formula (3):
[0093]
[0094] The preparation method of the photoinitiator B comprises the following steps:
[0095] 31.42g of fluorobenzene and 46.69g of aluminum chloride were dissolved in 1.5L of dichloromethane to obtain a first mixed solution, and then the first mixed solution was placed in a 2°C water bath. 49.05g of oxalyl chloroformate was dissolved in 0.7L of dichloromethane to obtain a second mixed solution, and the second mixed solution was dripped into the first mixed solution at a rate of 4mL / second and the first stirring of 350rpm was carried out simultaneously to carry out the first stage reaction. After the addition was completed, the temperature was raised to room temperature (35°C) and the second stage reaction was continued for 5 hours. After the first reaction was completed, the material after the first reaction was poured into 7L of deionized water at 5°C and stirred, the water layer was separated from the organic layer, and the water layer was extracted with dichloromethane, the organic layers were combined, washed with saturated brine, and then dried over anhydrous sodium sulfate to obtain an organic product. The organic product was uniformly mixed with 77.13 g of (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, the solvent was removed by distillation under reduced pressure, and the mixture was purified by silica gel column chromatography to obtain light yellow solid p-fluorobenzoylformate-acylphosphine oxide, with a total yield of 60.85% by mass.
[0096] The structural formula of the photoinitiator C is shown in formula (3):
[0097]
[0098] The preparation method of the photoinitiator C comprises the following steps:
[0099] 26.88g of fluorobenzene and 46.69g of aluminum chloride were dissolved in 1.5L of dichloromethane to obtain a first mixed solution, and then the first mixed solution was placed in a 10°C water bath. 27.44g of oxalyl chloroformate was dissolved in 0.7L of dichloromethane to obtain a second mixed solution, and the second mixed solution was dripped into the first mixed solution at a rate of 5mL / second and the first stirring of 300rpm was carried out simultaneously to carry out the first stage reaction. After the dropwise addition was completed, the temperature was raised to room temperature (20°C) and the second stage reaction was continued for 3 hours. After the first reaction was completed, the material after the first reaction was poured into 7L of deionized water at 5°C and stirred, the water layer was separated from the organic layer, and the water layer was extracted with dichloromethane, the organic layers were combined, washed with saturated brine, and then dried over anhydrous sodium sulfate to obtain an organic product. The organic product was uniformly mixed with 84.79 g of (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, the solvent was removed by distillation under reduced pressure, and the mixture was purified by silica gel column chromatography to obtain light yellow solid p-fluorobenzoylformate-acylphosphine oxide, with a total yield of 63.47% by mass fraction.
[0100] The structural formula of the photoinitiator D is shown in formula (4):
[0101]
[0102] The preparation process of photoinitiator D is the same as that of photoinitiator A except that fluorobenzene is replaced by an equal molar amount of chlorobenzene. The total yield based on mass fraction is 58.64%.
[0103] The structural formula of the photoinitiator E is shown in formula (5):
[0104]
[0105] The preparation process of photoinitiator E is the same as that of photoinitiator A except that fluorobenzene is replaced by an equal mole of benzene. The total yield based on mass fraction is 60.27%.
[0106] The structural formula of the photoinitiator F is shown in formula (6):
[0107]
[0108] In the preparation process of photoinitiator F, except that (2,4,6-trimethylbenzoyl)bis(p-tolyl)phosphine oxide was replaced by an equal mole of (2,4,6-trimethylbenzoyl)bis(phenyl)phosphine oxide, the rest was the same as that of photoinitiator A, and the total yield by mass fraction was 63.18%.
[0109] The structural formula of the photoinitiator G is shown in formula (7):
[0110]
[0111] The preparation process of photoinitiator G is the same as that of photoinitiator A except that fluorobenzene is replaced by an equal mole of iodobenzene. The total yield based on mass fraction is 56.97%.
[0112] Generally speaking, the present invention has no special requirements for the selection of colorants, and any colorant that can be used in 3D printing ceramic compositions that is well known to those skilled in the art can be used. For the convenience of experimental comparison, the colorants used in the following examples and comparative examples are 45wt% titanium dioxide, 23wt% yellow iron oxide, 27wt% red iron oxide, and 5wt% black iron oxide. The fillers used in the following examples and comparative examples are all silane-modified fillers, and the specific silane modification method is: KH570 hydrolysis silanization modification. The specific composition of barium glass powder is 27% barium oxide, 50% silicon dioxide, 10% boron oxide, 10% aluminum oxide, and 3% fluoride.
[0113] Example 1
[0114] The present embodiment provides a composition, which includes, based on 100 parts by total weight, 18 parts of dimethacrylate carbamate (oligomer), 6 parts of acryloylmorpholine (monofunctional free radical acrylate monomer), 10 parts of tripropylene glycol diacrylate (bifunctional free radical acrylate monomer), 3 parts of photoinitiator A, 60 parts of barium glass powder (filler), 2.5 parts of colorant (additive), and 0.5 parts of p-hydroxyanisole (additive).
[0115] This embodiment also provides a method for preparing the composition, and the specific steps include: mixing the raw material components according to the mass fraction ratio according to the formula amount, and the raw materials of the mixed composition include: first mixing the monomer and the photoinitiator, and then adding the oligomer, the additive and the filler in sequence, and then stirring at 1500 rpm for 1.5 hours at room temperature and in the dark to obtain the composition.
[0116] Example 2
[0117] The present embodiment provides a composition, which includes, based on 100 parts by total weight, 15 parts of epoxy acrylate (oligomer), 10 parts of triethylene glycol dimethacrylate (bifunctional free radical acrylate monomer), 10 parts of trimethylolpropane trimethacrylate (trifunctional free radical acrylate monomer), 4 parts of photoinitiator B, 58 parts of feldspar powder (filler), 2.5 parts of colorant (additive), and 0.5 parts of p-hydroxyanisole (additive).
[0118] This embodiment also provides a method for preparing the composition, and the specific steps include: mixing the raw material components according to the mass fraction ratio according to the formula amount, and the raw materials of the mixed composition include: first mixing the monomer and the photoinitiator, and then adding the oligomer, the additive and the filler in sequence, and then stirring at 1000 rpm for 2 hours at room temperature and in the dark to obtain the composition.
[0119] Example 3
[0120] This embodiment provides a composition, which includes, based on 100 parts by total weight, 16 parts of bisphenol A-dimethacrylate glycidyl ester (oligomer), 16 parts of isobornyl acrylate (monofunctional free radical acrylate monomer), 2.5 parts of photoinitiator C, 32.5 parts of sodium aluminum silicate powder (filler), 30 parts of barium glass powder (filler), 2.5 parts of colorant (additive), and 0.5 parts of p-hydroxyanisole (additive).
[0121] This embodiment also provides a method for preparing the composition, and the specific steps include: mixing the raw material components according to the mass fraction ratio according to the formula amount, and the raw materials of the mixed composition include: first mixing the monomer and the photoinitiator, and then adding the oligomer, the additive and the filler in sequence, and then stirring at 3000 rpm for 0.5h under room temperature and light-proof conditions to obtain the composition.
[0122] Example 4
[0123] This embodiment provides a composition, which comprises, based on 100 parts by total weight, 20 parts of bisphenol A-glycidyl dimethacrylate (oligomer), 30 parts of isobornyl acrylate (monofunctional free radical acrylate monomer), 4 parts of photoinitiator C, 42 parts of barium glass powder (filler), 3 parts of colorant (additive), and 1 part of p-hydroxyanisole (additive). The preparation method is the same as that of Example 1.
[0124] Example 5
[0125] This embodiment provides a composition, which includes, based on 100 parts by weight, 5 parts of dimethacrylate carbamate (oligomer), 12 parts of isobornyl acrylate (monofunctional free radical acrylate monomer), 1 part of photoinitiator A, 79.01 parts of barium glass powder (filler), 2 parts of colorant (additive), and 0.99 parts of p-hydroxyanisole (additive). The preparation method is the same as that of Example 1.
[0126] Example 6
[0127] This embodiment provides a composition, which is the same as that of Embodiment 1 except that the weight portion of the photoinitiator A is 5 parts and the weight portions of other components are reduced in proportion, and will not be described again.
[0128] Example 7
[0129] This embodiment provides a composition, which is the same as that of Embodiment 1 except that no oligomer is added and the mass fraction of the oligomer is distributed to other components in proportion, and will not be described in detail here.
[0130] Example 8
[0131] This embodiment provides a composition, which is the same as that of Embodiment 1 except that the photoinitiator A is replaced by the photoinitiator D, and will not be described in detail here.
[0132] Example 9
[0133] This embodiment provides a composition, which is the same as that of Embodiment 1 except that the photoinitiator A is replaced by the photoinitiator E, and will not be described in detail here.
[0134] Example 10
[0135] This embodiment provides a composition, which is the same as that of Embodiment 1 except that the photoinitiator A is replaced by the photoinitiator F, and will not be described in detail here.
[0136] Embodiment 11
[0137] This embodiment provides a composition, which is the same as that of Embodiment 1 except that the photoinitiator A is replaced by the photoinitiator G, and will not be described in detail here.
[0138] Comparative Example 1
[0139] This comparative example provides a composition, which is the same as Example 1 except that the photoinitiator A is replaced by (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, and the rest is not repeated here.
[0140] Comparative Example 2
[0141] This comparative example provides a composition, which is the same as Example 1 except that the photoinitiator A is replaced by di(4-methylphenyl)phosphine oxide, and the rest is not repeated here.
[0142] Application Example 1
[0143] This application example provides an application of a composition in 3D printing composite ceramics, and the application includes:
[0144] The composition provided in Example 1 was used for 3D printing. The 3D printing was performed at 405 nm. The printing chamber started the heating function and the hot air circulated inside the hot air blower at 33 ° C to complete the primary curing. The secondary curing was post-processing of the light source at 405 nm. The light power of the curing box was 150 mw / cm 2 The secondary curing time was 15 minutes, and a high-density double-network printed composite ceramic crown and bridge material was obtained.
[0145] Application Example 2
[0146] This application example provides an application of a composition in 3D printing composite ceramics, and the application includes:
[0147] The composition provided in Example 1 was used for 3D printing. The 3D printing was performed at 405 nm. The printing chamber started the heating function and the hot air circulated inside the hot air blower at 40 ° C to complete the primary curing. The secondary curing was post-processing at 405 nm. The light power of the curing box was 200 mw / cm 2 The secondary curing time is 10 minutes, and a high-density double-network printed composite ceramic crown and bridge material is obtained.
[0148] Application Example 3
[0149] This application example provides an application of a composition in 3D printing composite ceramics, and the application includes:
[0150] The composition provided in Example 1 was used for 3D printing. The 3D printing was performed at 385 nm. The printing chamber started the heating function and the hot air circulated inside the hot air blower at 20 ° C to complete the primary curing. The secondary curing was post-processing of the light source in the 385 nm band. The light power of the curing box was 50 mw / cm 2 The secondary curing time is 20 minutes, and a high-density double-network printed composite ceramic crown and bridge material is obtained.
[0151] Application Examples 4 to 11 and Comparative Application Examples 1 to 2
[0152] Application Examples 4 to 11 and Application Comparative Examples 1 to 2 provide an application of a composition in 3D printing composite ceramics. The application of the composition in 3D printing composite ceramics is the same as Application Example 1 except that the compositions in Examples 4 to 11 and Comparative Examples 1 to 2 are respectively used, and will not be repeated here.
[0153] Test method:
[0154] Bending strength: ISO10477-YY0710 "Polymer-based crown and bridge materials for dentistry"
[0155] Flexural modulus: ISO10477-YY0710 "Polymer-based crown and bridge materials for dentistry"
[0156] Fracture toughness: 20795-2-YY0270.2 "Dental base polymers Part 2: Orthodontic base polymers"
[0157] Vickers hardness: ISO6507.1-GB / T4340.1 "Vickers hardness test for metallic materials - Part 1: Test method"
[0158] Water absorption value: ISO4049-YY1042 "Polymer-based restorative materials for dentistry"
[0159] Dissolution value: ISO4049-YY1042 "Polymer-based restorative materials in dentistry"
[0160] Anti-staining: YY / T1932-2024 "Dentistry Diaphragm-type Bracketless Orthodontic Appliances"
[0161] The test results of the above application examples and application comparison examples are shown in Table 1.
[0162] Table 1
[0163]
[0164] From Table 1, we can see the following points:
[0165] (1) It can be seen from the application examples 1 to 4 that the photoinitiator provided by the present invention has excellent mechanical properties when used as a dental restoration material. Specifically, the flexural strength is above 200 MPa, the flexural modulus is above 8.5 GPa, the fracture toughness is above 2.51 MPa·m1 / 2, the Vickers hardness is above 33.88 HV, and the water absorption value is low, which is only 17.08 μg / mm 3 The solubility value is only 1.71μg / mm 3 The anti-staining difference is within 1.8, and the anti-staining ability is strong.
[0166] (2) It can be seen from the combined application examples 1 and 6 that the addition of 3 parts of photoinitiator in application example 1 is better than that of 5 parts of photoinitiator in application example 6 in color stability and anti-staining performance of the product in application example 1. This shows that the present invention preferably controls the amount of photoinitiator added within a reasonable range, which can better improve product performance;
[0167] (3) It can be seen from the combination of Application Example 1 and Application Example 7 that when no oligomer is added in Application Example 7, the mechanical properties of the product deteriorate, and the strength and hardness decrease significantly;
[0168] (4) Application Examples 8, 9, 10, and 11 corresponding to photoinitiators D, E, F, and G with different structures have certain mechanical properties and aesthetic properties compared to Comparative Examples 1 to 2, but are inferior to Application Example 1. Specifically, X in Application Example 8 is chlorine, X in Application Example 11 is iodine, Application Example 9 does not contain X, and X in Application Example 1 is fluorine. The F bond in Application Example 1 has a similar effect to low surface energy, has a better anti-staining effect, and has significantly better mechanical properties; Application Example 10 contains a phenyl-phosphorus chemical bond, which has a biosafety risk and is difficult to be used in dental materials, and has relatively worse mechanical properties and anti-staining properties.
[0169] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A photoinitiator, characterized in that The structural formula of the photoinitiator is shown in formula (1): In formula (1), X is a halogen element or hydrogen, R1 and R2 are each independently any one of substituted and / or unsubstituted phenyl and / or hydrocarbon groups, and Y1 and Y2 are each independently a branched or straight-chain hydrocarbon group.
2. The photoinitiator according to claim 1, characterized in that In the formula (1), X includes any one of fluorine, bromine, chlorine or iodine; Preferably, R1 and R2 are each independently substituted and / or unsubstituted phenyl, preferably p-methylphenyl; Preferably, Y1 and Y2 are each independently an alkane group having 1 to 5 carbon atoms, preferably a methyl group.
3. A method for preparing the photoinitiator according to claim 1 or 2, characterized in that: The preparation method comprises: The oxalyl chloride ester and the halogenated benzene are first reacted to prepare the p-halogenated benzene acyl ester; The p-halogenated benzoyl ester and the structure represented by formula (2) undergo a second reaction to prepare a photoinitiator represented by the structure of formula (1); In formula (2), R3 is an aromatic hydrocarbon group.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The oxalyl chloride ester is oxalyl chloroformate; Preferably, the p-halobenzoyl ester is p-halobenzoyl formate; Preferably, in the structure represented by formula (2), R3 is any one of substituted phenyl, benzyl or phenethyl, or a combination of at least two thereof.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the oxalyl chloride to the halogenated benzene is 1.02-1.6:1; Preferably, the mass ratio of the structure represented by formula (2) to the p-halogenated benzoyl ester is 2.3 to 3.2:1; Preferably, the first reaction is carried out under the catalysis of a catalyst; Preferably, the catalyst comprises aluminum chloride; Preferably, the mass ratio of the aluminum chloride to the halogenated benzene is 1.4-1.75:
1.
6. A composition, characterized in that The composition comprises the photoinitiator according to claim 1 or 2, and / or a photoinitiator prepared by the method for preparing the photoinitiator according to any one of claims 3 to 5.
7. The composition according to claim 6, characterized in that The composition also includes oligomers, monomers and fillers; Preferably, the mass fraction of the oligomer in the composition is 5 to 20%; Preferably, the mass fraction of the monomer in the composition is 12 to 30%; Preferably, the mass fraction of the photoinitiator in the composition is 1 to 4%; Preferably, the mass fraction of filler in the composition is 42-80%.
8. The composition according to claim 7, characterized in that The oligomers include oligomeric acrylate derivatives; Preferably, the monomer comprises a free radical acrylate monomer having at least one functional group.
9. Use of the composition according to any one of claims 6 to 8 in dental restorative materials.
10. The use according to claim 9, characterized in that: The composition is used to prepare ceramic crown and bridge materials; Preferably, the preparation comprises: curing the composition to obtain a ceramic crown and bridge material; Preferably, the curing comprises 3D printing light curing; Preferably, the curing further comprises secondary curing after 3D printing light curing; Preferably, the secondary curing comprises: 3D printing light-cured material at a light power of 50 to 200 mW / cm 2 Secondary curing is carried out under the conditions of.
Citation Information
Patent Citations
Novel bifunctional benzoyl formic acid hydroxy ketone ester compounds and photoinitiators containing the compounds
CN103709036A